Padrões fenológicos e atributos reprodutivos de espécies lenhosas no cerrado do Estado do Maranhão, Brasil - LACERDA, Dinnie Michelle Assunção (2017)
Phenological studies at the community level in areas with scarce information may contribute to a more comprehensive understanding of the dynamics of plant communities. Such studies also allow the focus on groups of species that can bring important advances to lines more specifics of knowledge regarding phenology. Thus, with the overall objective to determine the phenological pattern of woody plant communities in two cerrado areas in the State of Maranhão, it was conducted the present study. The collection areas, in cerrado stricto sensu, are located in the Barreirinhas and at Mirador State Park (MSP), Maranhão State. It were estimated visually the percentage data regarding leaf production, leaf fall, flowering and fruiting during 24 months, monthly, in individuals with trunk circumference at the soil level >10 cm. It was marked 1418 individuals, being 706 in Barreirinhas, beloging to 43 species, and 712 at MSP, represented by 65 species. Statistical tests used included Rayleigh and Watson Williams analyses, median differences (Mann-Whitney) and distributions (G-tests). The Chapter I (to be submitted to the Brazilian Journal of Botany) deals with the characterization and comparison of the two communities, whose results show a higher concentration of leaf fall events and production events (leaf and flower) during the dry season for both areas. At the beginning of the rainy season, the production of new leaves and fruiting, which increase since the end of the dry period, remain intense. The dispersion syndromes show a close relationship with the responses found for fruiting, predominating the zoocoria in both areas. The chapter II (accepted by Flora Journal) evaluates five populations with wide occurrence in cerrado areas, present in both areas, seeking to investigate whether responses at the populations differ between areas and show similar behavior to the communities in which they are inserted, thus excluding possible effects related to differences in species composition between areas. The responses found in the two chapters are similar, with conspecific communities or populations showing adjustments to local variables, mainly related to temperature and photoperiod, associated to differences in occurrence in the period of drought in each area. Phenophases occur or intensify earlier in the MSP, showing the adjustments to the local climatic conditions and contributing with information on the plasticity of the species in different abiotic conditions. The third article (submitted to the Acta Botanica Brasilica) evaluates the relationship between reproductive phenology of evergreen (EG) and deciduous (DEC) species in MSP. Were found differences in reproductive attributes between the EG and DEC groups in relation to flowering, indicating the early occurrence and longer duration of phenological events in EG in relation to DEC. For fruiting, the main differences between DEC and EG were related to the different distribution ofviii activity percentage between the groups and their greater intensity in the EG. These responses reflect different strategies of water use by these groups. Therefore, this study provides ecological information previously non-existent in this region and little addressed in the cerrado area, contributing to the understanding of phenological responses and their associations with climate.